PENGUNGKAPAN ISLAMIC CORPORATE SOCIAL RESPONSIBILITY (ICSR) DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING) - Utami, Reistiawati; Yusniar, Meina Wulansari (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2020)
The company maintains its existence by maintaining the company's financial performance and establishing its good relations to its stakeholders. Islamic Corporate Social Responsibility (ICSR) and Good Corporate Governance (GCG) are forms of corporate responsibility towards its stakeholders. This study aims to analyze the effect of disclosures of ICSR and GCG on the Company Profitability and the Company Value through Company Profitability.The proxy variables used are the ISR Index (Islamic Social Reporting), the GCG Index sourced from KNKG and OJK, ROE and PBV. Companies chosen as the sample of research are those included in JII for the period 2016 - 2018. Data analysis and hypothesis testing were conducted through the Mediation effect Regression technique by using the SEM - PLS algorithm generated by Smart PLS 3.0 software.The results showed that (1) ICSR had a negative and insignificant effect on Company Financial Performance, (2) ICSR had a negative insignificant effect on Company Value, (3) GCG had a significant positive effect on Company Financial Performance, (4) GCG had a positive and significant effect on Company Value,(5) Financial Performance had a significant and positive effect on Company Value,(6) Financial Performance could not mediate the relationship of ICSR influence on Company Value, and (7) Financial Performance could mediate the relationship of GCG influence towards Company Value.